Pendidikan Kesehatan tentang Tuberkulosis terhadap Peningkatan Pengetahuan dan Sikap Penderita dalam Pencegahan Penularan Tuberkulosis - Susanto, Wibowo Hanafi Ari; Wospakrik, Frengki; Mulyanti, Mulyanti; Rahmawati, Rahmawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to evaluate the effect of health education on increasing patient knowledge and attitudes to prevent tuberculosis transmission at the Nabire District Health Center, Nabire Regency. This research method uses a Quasi-Experimental Pre-Post design with case and control groups. The research showed that the experimental group experienced a significant increase in their knowledge (an average of 50.48 on the pre-test to 77.14 on the post-test). The control group also experienced a rise, although smaller (an average of 49.02 on the pre-test to an average of 50.40 on the post-test). Changes in the attitudes of respondents in both groups also occurred, with a significant increase in the experimental group (average of 47.72 in the pre-test to 72.70 in the post-test) and a minor increase in the control group (average of 47.96 in the pre-test to 51.60 on post-test). Based on the results of the bivariate analysis, it was found that the P-value was 0.000, which means that there was an influence of health education about tuberculosis on increasing the knowledge and attitudes of sufferers in preventing the transmission of tuberculosis. In conclusion, the health education approach effectively increases patient knowledge and attitudes toward avoiding tuberculosis. These results indicate the need to integrate health education to control tuberculosis in the Nabire District Health Center and similar areas. Keywords: Health Education, Knowledge, Attitude, Tuberculosis